Comparison of three screening tools to detect psoriatic arthritis in patients with psoriasis (CONTEST study). (25th March 2013) - Coates, L.C.; Aslam, T.; Al Balushi, F.; Burden, A.D.; Burden‐The, E.; Caperon, A.R.; Cerio, R.; Chattopadhyay, C.; Chinoy, H.; Goodfield, M.J.D.; Kay, L.; Kelly, S.; et al.
Summary Background Multiple questionnaires to screen for psoriatic arthritis (PsA) have been developed but the optimal screening questionnaire is unknown. Objectives To compare three PsA screening questionnaires in a head‐to‐head study using CASPAR (the Classification Criteria for Psoriatic Arthritis) as the gold standard. Methods This study recruited from 10 U.K. secondary care dermatology clinics. Patients with a diagnosis of psoriasis, not previously diagnosed with PsA, were given all three questionnaires. All patients who were positive on any questionnaire were invited for a rheumatological assessment. Receiver operating characteristic (ROC) curves were used to compare the sensitivity, specificity and area under the curve of the three questionnaires according to CASPAR criteria. Results In total, 938 patients with psoriasis were invited to participate and 657 (70%) patients returned the questionnaires. One or more questionnaires were positive in 314 patients (48%) and 195 (62%) of these patients attended for assessment. Of these, 47 patients (24%) were diagnosed with PsA according to the CASPAR criteria. The proportion of patients with PsA increased with the number of positive questionnaires (one questionnaire, 19·1%; two, 34·0%; three, 46·8%). Sensitivities and specificities for the three questionnaires, and areas under the ROC curve were, respectively: Psoriatic Arthritis Screening Evaluation (PASE), 74·5%, 38·5%, 0·594; Psoriasis Epidemiology Screening Tool (PEST), 76·6%, 37·2%, 0·610; Toronto Psoriatic Arthritis Screen (ToPAS), 76·6%, 29·7%, 0·554. The majority of patients with a false positive response had degenerative or osteoarthritis. Conclusion Although the PEST and ToPAS questionnaires performed slightly better than the PASE questionnaire at identifying PsA, there is little difference between these instruments. These screening tools identify many cases of musculoskeletal disease other than PsA.